Comprehensive Inpatient Rehabilitation Protocol for Acquired Diaphragmatic Hernia Repair: A Case Report - Athwale, Reema Mohan; Shukla, Manish Prannath (Journal of Health and Allied Sciences NU, 2024)
This case report presents a comprehensive rehabilitation approach for a 32-year-old female patient who underwent diaphragmatic hernia repair. The rehabilitation protocol aimed to improve postoperative recovery, promote independence, and enhance the patient's quality of life. The study outlines a 2-week treatment plan with specific goals and interventions for each phase. Our findings reveal promising outcomes, demonstrating the positive impact of rehabilitation on postoperative recovery. The rehabilitation interventions not only contributed to enhanced diaphragmatic muscle mobility, vital parameters, chest expansion, pulmonary function, and respiratory muscle strength but also lead to improved breathing patterns. The outcomes of this study emphasize the crucial role of customized rehabilitation programs in maximizing respiratory function, fostering mobility, mitigating complications, and facilitating functional recovery. Through a comprehensive case report, we showcase the efficacy of integrating tailored rehabilitation strategies into the postoperative care paradigm in promoting overall recovery and elevating the well-being of individuals undergoing diaphragmatic hernia repair.
Keywords: diaphragmatic hernia; hernia rehabilitation; traumatic acquired hernia